Predictors of Short and Long-Term Success of Electrical Cardioversion in Persistent Atrial Fibrillation - Ahmad, Hira; Shabbir , Muhammad; Mushtaq, Huma; Mukarram, Shahid; Fahd, Tehreem; Sajidain Syed, Syed (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the predictors of short-term and long-term success of electrical cardioversion in persistent atrial fibrillation. Study Design: Prospective longitudinal study. Place and Duration of Study: Department of Cardiology, Electrophysiology Division, Armed Forces Institute of Cardiology & National Institute of Heart Diseases (AFIC-NIHD), Rawalpindi Pakistan, from Sep 2024 to Apr 2025. Methodology: A total of 119 male and female patients aged 20 to 90 years diagnosed with persistent atrial fibrillation. Patients with valvular heart disease, prior history of electrical cardioversion, paroxysmal atrial fibrillation, and left atrial clot were excluded. Electrical cardioversion was performed, and short-term (sinus rhythm restoration after a week) and long-term (sinus rhythm restoration after three months) success was noted. Data analysis was carried out using Statistical Package for the Social Sciences (SPSS) version 26. Results: The mean age of the participants was 55.95±11.46 years, and the mean Atrial Fibrillation (AF) duration was 12.63±3.72 days. Patients aged more than 50 years were 77(64.7%), and 72(60.5%) patients were male. Successful cardioversion was recorded in 104 patients (87.4%). Short-term and long-term success was recorded in 92(77.3%) and 80(67.2%) patients, respectively. Acute successful cardioversion was more frequent when performed by a consultant with more than 12 years of experience (91.0% versus 76.7%, p-value 0.041). Conclusion: Electrical cardioversion was shown to be an effective and successful therapy for persistent atrial fibrillation. Although success rates inevitably declined over time, the promising early outcomes demonstrate that electrical cardioversion is a dependable first-line technique for restoring sinus rhythm.